Buddha aura Bauddha sādhaka : Bhagavān Buddha aura unake katipaya śishya-śishyāoṃ kī jīvana-smr̥tiyām̐ - Upādhyāya, Bharatasiṃha, 1915-1990 (Sasthā Sāhitya Maṇḍala Prakāśana, 1950)
Collective biography of disciples of Gautama Buddha.